Performance indicators during international rugby union matches are influenced by a combination of physiological and contextual variables - Liam Kilduff (Journal of Science and Medicine in Sport, 2020)
ObjectivesResearch has linked physiological (e.g., hormonal, affective, fatigue) outcomes to performance indicators in rugby competition, but no work has integrated and contextualised these factors within a test-match environment. We addressed this gap by monitoring 29 athletes from a training squad across eight international rugby matches.MethodsPre-match (8-9 am) measures of salivary testosterone and cortisol concentrations, sleep duration, pulse rate, muscle soreness, stress, mood, and motivation were taken. Contextual factors were playing time, internal training load (ITL), test-match experience, opponent ranking, and crowd size. Performance was indexed by coach and player ratings of performance (CRP, PRP) and quantitative metrics; offloads, turnovers, runs with ball in hand (RWB), tackles, passes, and defenders beaten (DFB).ResultsMorning cortisol, sleep and mood were positively related to CRP and PRP (standardised coefficient estimates from 0.17 to 0.22). Cortisol, sleep, stress, mood and motivation were associated with one (or more) of turnovers, RWB, tackles, passes and DFB (incidence rate ratio [IRR] from 0.74 to 1.40). Playing time was positively related to all quantitative performance indicators (IRR from 1.01 to 1.04) with ITL, opponent ranking, and crowd size predicting selected outputs (IRR from 0.89 to 1.15). The explanatory models varied (conditional R2 = 0.15 to 0.83) but were generally stronger with both physiological and contextual inputs.ConclusionsMultiple physiological and contextual factors appear to contribute to player performance in international rugby competition. Measurement of these factors may guide training and management practices, a potential practical consequence but also advancing understanding from marker to causal link.